Pragmatic Analysis of Speech Acts in Short Dialogue of Listening Comprehension Test - Fransisco Padang; Dita Veny Mutiara Purba; Erikson Saragih (Jurnal Ilmiah Profesi Pendidikan, 2022)
Listening comprehension is regarded as one of the most challenging tasks for students and the majority of students struggle to grasp the proposed meaning in TOEFL short dialogue of listening comprehension test items. The utterances in TOEFL short dialogue test can be analyzed using pragmatic through speech act classification by J. Searle. This study aims to investigate the kind sand the dominant type of speech act in TOEFL short dialogue of listening comprehension test. The study uses a qualitative descriptive approach with a content analysis research design to reach the objectives of this research. The objects were taken through 30 short dialogues in TOEFL listening test items. The results of the study show the distribution of each classification found as the following: 44% for directive, 42% for assertive, 11,5% for expressive, and 1% for commisive. It can be seen that the most dominant type is directive and commissive is less found. The study concludes that test takers must be familiar with the context of the speech to comprehend the proposed meaning of the TOEFL listening items. It is recommended for students to evaluate the meaning of the utterances using the speech acts theories to assist the students in identifying the different sorts of utterances and understanding the proposed meaning of the utterances.